FILSAFAT ILMU DALAM PENGKAJIAN ISLAM: MEMBANGUN FORMAT EPISTEMOLOGI KAJIAN ISLAM MELALUI REKONSTRUKSI PEMIKIRAN M. ABED AL-JABIRI - Yurna Bachtiar; Muhamad Naufal Firdaus; Irawati; Arif Saipullah; Muhammad Helmi Alfian; U. Ruhimatullah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
The study of Islam in a modern context requires epistemological renewal to address contemporary challenges. Muhammad Abed al-Jabiri, a contemporary thinker from Morocco, offers a reconstruction of Arab-Islamic epistemology through his project Naqd al-'Aql al-'Arabi (Critique of Arab Reason). This research aims to examine the role of philosophy of science in developing Islamic epistemology by highlighting al-Jabiri's thought. The research method employed is qualitative research with a library research approach, collecting data from various relevant primary and secondary literature. The results show that al-Jabiri identifies three epistemological systems in Islamic tradition: bayani (text-based), irfani (mystical experience-based), and burhani (rationality-based). The main problem is the hegemonic dominance of bayani epistemology that causes stagnation in Islamic thought. Al-Jabiri proposes a circular integration model where the three epistemologies can dialogue and complement each other constructively. This research concludes that philosophy of science serves as a methodological foundation for the emergence of critical, adaptive, and transformative Islamic studies toward contemporary social realities. The reconstruction of Islamic epistemology through the philosophy of science approach enables the development of Islamic scholarship that is not only faithful but also scientifically minded and oriented toward civilizational advancement, capable of integrating textual, spiritual, and rational dimensions into a harmonious unity